Ethnomusicology: Issues and Possibilities - Majid Hamdoon Al Harthy (Journal of Arts and Social Sciences, 2015)
This study investigates and analyzes the relationship between the development of the field of Ethnomusicology in United States, since the 1950s, and its predecessor known as Comparative Musicology, which emerged during the last two decades of 19th century Germany. Tracing the theoretical bases for Comparative Musicology, it becomes clear that certain fundamental issues caused researchers to distance themselves from the ideologies of traditional musics that, eventually, led to the emergence of Ethnomusicology. Furthermore, by exploring certain aspects of Comparative Musicology and Ethnomusicology, one cannot but notice the central role publications played in the establishment of both fields. However, unlike Comparative Musicology, which adopted a comparative approach to analysis; modern ethnomusicology called for the embracement of the musics of the «other» and the recognition of their contextual uniqueness before comparing them to other musical systems. Thus, the modern ethnomusicologist always seeks to associate him/herself to the musics of the «other» not only for the sake of understanding musical elements and structures, but also in order to gain a deeper understanding of the social and cultural aspects of the communities producing the music.